2008
DOI: 10.1177/1470595807088322
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood to Sexually Harass

Abstract: Perceptual differences between men and women in what constitutes sexual harassment have been studied extensively (Rotundo et al., 2001), but the sexual harassment literature has been critiqued on the ground that it often neglects important cultural dimensions ABSTRACT We tested hypotheses regarding the association of national culture with the likelihood to sexually harass by comparing samples of male and female international students. Our hypotheses were derived from implications of Hofstede's cross cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 45 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…Women were proposed to tolerate SBH to a greater degree in societies with these cultural values. Consistent with these predictions, men in China and India exhibit higher levels of LSH than men in the United States (Luthar & Luthar, 2008); women in Brazil experience more sexual harassment than women in the United States (Gelfand et al, 1995); and people in Ecuador, Pakistan, the Philippines, Taiwan, and Turkey are less likely than people in Canada, Germany, the Netherlands, and the United States to interpret unwanted sexual attention from a superior as harassment (Sigal et al, 2005). However, not all studies have supported Luthar and Luthar's predictions (e.g., Shaffer et al, 2000, found no consistent patterns across Hong Kong, Beijing, and the United States).…”
Section: Prevalence By Societal Contextsupporting
confidence: 54%
“…Women were proposed to tolerate SBH to a greater degree in societies with these cultural values. Consistent with these predictions, men in China and India exhibit higher levels of LSH than men in the United States (Luthar & Luthar, 2008); women in Brazil experience more sexual harassment than women in the United States (Gelfand et al, 1995); and people in Ecuador, Pakistan, the Philippines, Taiwan, and Turkey are less likely than people in Canada, Germany, the Netherlands, and the United States to interpret unwanted sexual attention from a superior as harassment (Sigal et al, 2005). However, not all studies have supported Luthar and Luthar's predictions (e.g., Shaffer et al, 2000, found no consistent patterns across Hong Kong, Beijing, and the United States).…”
Section: Prevalence By Societal Contextsupporting
confidence: 54%
“…The model has been developed and applied primarily in anthropological and sociological contexts (Basu, 2003; Hofstede, 1994). In cross‐cultural research, the use of Hofstede's framework has been limited to macrolevel inquiries concerned with identifying cultural predictors of social and economic trends, such as corruption rates (Cheung & Chan, 2008), sexual harass (Luthar & Luthar, 2008), work motivation (Barbuto & Gifford, 2007), and gender inequality (Cheung, 2007). We think that our study expanded Hofstede's theoretical model by introducing previously underexplored technological dimensions, such as hyperlinking and blogging.…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers have endeavored to identify the characteristics of male sexual harassers (e.g., Begany & Milburn, 2002;Krings & Facchin, 2009;Luthar & Luthar, 2008;Pryor, 1987;Stillman, Yamawaki, Ridge, White, & Copley, 2009), less research has examined the motives driving sexual harassment. And almost no research has focused on the cognition of the sexual harassment perpetrator and the self-regulatory processes which inhibit and facilitate harassing behavior.…”
Section: Moral Disengagement In Sexual Harassmentmentioning
confidence: 99%